Efektivitas Sistem Informasi Pembangunan Daerah (SIPD) dalam Perencanaan Pembangunan Daerah - Mahathir Muhammad Iqbal; Sri Handayani; Dewi Istanti Safitri (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
Development is a continuous effort in creating conditions that can provide more valid (valid) alternatives for every citizen to achieve his most humanist aspirations, generally humanist aspirations are expressed as increasing social welfare. Therefore, a development must begin with proper planning. So that with a proper planning will provide a development result in accordance with the needs of the community. The Malang Regency Government itself only implemented SIPD in early 2021, so that at a very young age, of course, there are still many things that need to be improved in the future. The need for an evaluation of a program running is one way so that errors or deficiencies can be identified and corrected. Therefore, the author uses indicators from the theory of effectiveness that have been described in the theoretical study.